Improving Medical Education in Oncology: Enhancing Students’ Understanding of Cancer Treatments Through Multidisciplinary Clinical Rotations - Arnaud Beddok; Leila Bouazzi; Coralie Barbe; Pierre Martin; Julian Gratiaux; Philippe Guilbert; Louis Job; Amélie Lemoine; David Morland; Dimitri Papathanassiou; Stéphane Perin; Yacine Merrouche; et al. (Journal of Cancer Education, 2025)

HydroBOT: an integrated toolkit for assessment of hydrology-dependent outcomes - Galen Holt; Georgia K. Dwyer; David Robertson; Martin Job; Rebecca E. Lester (Environmental Modelling & Software, 2025)

Soil and leaf phosphorus thresholds for modern potato production systems in tropical Oxisols - Rogério P. Soratto; Patricio Sandaña; Adalton M. Fernandes; Tassiane S. Calles; Renato Yagi; Emerson F.C. Souza; André L.G. Job; Jéssyca D.L. Martins (European Journal of Agronomy, 2023)

Biosynthesis of silver nanoparticles of Tribulus terrestris food supplement and evaluated antioxidant activity and collagenase, elastase and tyrosinase enzyme inhibition: In vitro and in silico approaches - Célia Cristina Malaguti Figueiredo; Amanda da Costa Gomes; Laura Camargo Zibordi; Filipe Oliveira Granero; Valdecir Farias Ximenes; Nathalia Mariana Pavan; Luciana Pereira Silva; Cibely da Silva Martin Sonvesso; Aldo Eloizo Job; Nilson Nicolau-Junior; Regildo Márcio Gonçalves da Silva (Food and Bioproducts Processing, 2023)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

A High-Resolution Global Dataset of Extreme Sea Levels, Tides, and Storm Surges, Including Future Projections - Sanne Muis; Maialen Irazoqui Apecechea; Job Dullaart; Joao de Lima Rego; Kristine Skovgaard Madsen; Jian Su; Kun Yan; Martin Verlaan (Frontiers in Marine Science, 2020)

A behavioral economic analysis of the effects of rimcazole on reinforcing effects of cocaine injection and food presentation in rats - Martin O. Job; Jonathan L. Katz (Psychopharmacology, 2019)

Molecular Adaptations in the Rat Dorsal Striatum and Hippocampus Following Abstinence-Induced Incubation of Drug Seeking After Escalated Oxycodone Self-Administration - Christopher A. Blackwood; Reece Hoerle; Michael Leary; Jennifer Schroeder; Martin O. Job; Michael T. McCoy; Bruce Ladenheim; Subramaniam Jayanthi; Jean Lud Cadet (Molecular Neurobiology, 2019)

Specific activation of operculum 3 (OP3) brain region during provoked tinnitus-related phantom auditory perceptions in humans - Agnès Job; Roland Jacob; Yoann Pons; Marc Raynal; Michel Kossowski; Jérôme Gauthier; Bertrand Lombard; Chantal Delon-Martin (Brain Structure and Function, 2016)

μ-Opioid receptors in the stimulation of mesolimbic dopamine activity by ethanol and morphine in Long-Evans rats: a delayed effect of ethanol - John P. Valenta; Martin O. Job; Regina A. Mangieri; Christina J. Schier; Elaina C. Howard; Rueben A. Gonzales (Psychopharmacology, 2013)

Fungi, bacteria and soil pH : the oxalate–carbonate pathway as a model for metabolic interaction - Gaëtan Martin; Matteo Guggiari; Daniel Bravo; Jakob Zopfi; Guillaume Cailleau; Michel Aragno; Daniel Job; Eric Verrecchia; Pilar Junier (Environmental Microbiology, 2012)
Summary The oxalate–carbonate pathway involves the oxidation of calcium oxalate to low‐magnesium calcite and represents a potential long‐term terrestrial sink for atmospheric CO 2 . In this pathway, bacterial oxalate degradation is associated with a strong local alkalinization and subsequent carbonate precipitation. In order to test whether this process occurs in soil, the role of bacteria, fungi and calcium oxalate amendments was studied using microcosms. In a model system with sterile soil amended with laboratory cultures of oxalotrophic bacteria and fungi, the addition of calcium oxalate induced a distinct pH shift and led to the final precipitation of calcite. However, the simultaneous presence of bacteria and fungi was essential to drive this pH shift. Growth of both oxalotrophic bacteria and fungi was confirmed by qPCR on the frc (oxalotrophic bacteria) and 16 S rRNA genes, and the quantification of ergosterol (active fungal biomass) respectively. The experiment was replicated in microcosms with non‐sterilized soil. In this case, the bacterial and fungal contribution to oxalate degradation was evaluated by treatments with specific biocides (cycloheximide and bronopol). Results showed that the autochthonous microflora oxidized calcium oxalate and induced a significant soil alkalinization. Moreover, data confirmed the results from the model soil showing that bacteria are essentially responsible for the pH shift, but require the presence of fungi for their oxalotrophic activity. The combined results highlight that the interaction between bacteria and fungi is essential to drive metabolic processes in complex environments such as soil.